2013
DOI: 10.2146/ajhp120238
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing diabetes care by adding a pharmacist to the primary care team

Abstract: The addition of a pharmacist to an HMO primary care team improved short-term surrogate markers as well as long-term cardiovascular risk in adult patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 25 publications
(29 reference statements)
3
95
1
Order By: Relevance
“…Ip et al reported that intervention by pharmacists in primary care led to a decrease of HbA1c level after 12 months. 8) This report supports the need for pharmacists to participate in the treatment of ambulatory diabetic patients. In addition, Spence et al reported that improvement of adherence and a decrease of HbA1c level were achieved by faceto-face counseling of patients with poor glycemic control.…”
Section: Introductionsupporting
confidence: 61%
“…Ip et al reported that intervention by pharmacists in primary care led to a decrease of HbA1c level after 12 months. 8) This report supports the need for pharmacists to participate in the treatment of ambulatory diabetic patients. In addition, Spence et al reported that improvement of adherence and a decrease of HbA1c level were achieved by faceto-face counseling of patients with poor glycemic control.…”
Section: Introductionsupporting
confidence: 61%
“…Projected long-term cardiovascular risk was also significantly decreased in the intervention arm receiving pharmacist care. In this model, uncontrolled diabetics with A1c ≥7% were referred by the primary care team to the pharmacist for more stringent follow-up; the pharmacist performed pharmacotherapy adjustments under collaborative practice agreement (Ip et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diabetes management, studies have shown that CMM leads to significant reductions in hemoglobin A1c compared to control arms with estimated treatment differences ranging from -0.4% to -1.7%. [14][15][16][17][18] Moreover, several studies have demonstrated CMM's positive impact on all-or-none diabetes composite scores that involve achievement of several important treatment goals including smoking cessation, daily aspirin use, and meeting A1c, low density lipoprotein (LDL), and blood pressure goals. [5][6][7]15 Some studies of well-adopted CMM services have even demonstrated a positive impact on lowering patient total cost of care by decreasing hospitalizations and other acute care utilization.…”
Section: Introductionmentioning
confidence: 99%